A NEW RECORD CV TWO PENAEID SPECIES FROM GOA COAST - ACHUTHANKUTTY, C. T.; NAIR, S. R. SREEKUMARAN (Journal of Indian Fisheries Association, 2015)
Adults of Penaeus japonicus (Bate) and juveniles of P. canaliculatus (Olivier) were recordedfor the first time from the coastal and estuarine regions of Goa respectively. Their presence inGoa waters suggests that both the species have a wide distribution along the west coast of India.The available data from the neighbouring states suggest that both the species are distributedin deeper waters and are caught during or immediately after the southwest monsoon. Hence,it may be possible to tap these valuable resources from Goa waters if the fishing operation isextended to depths beyond those presently fished and fishing is carried out during the SWmonsoon season